Beyond Head and Neck Cancer: The Relationship Between Oral Microbiota and Tumour Development in Distant Organs - Mascitti, Marco; Togni, Lucrezia; Troiano, Giuseppe; Caponio, Vito Carlo Alberto; Gissi, Davide Bartolomeo; Montebugnoli, Lucio; Procaccini, Maurizio; Lo Muzio, Lorenzo; Santarelli, Andrea (Frontiers in Cellular and Infection Microbiology, 2019)
An altered oral microbiota has been linked with the development of several oral diseases, such as dental caries, periodontal disease, and oral stomatitis. Moreover, poor oral health has been linked to head and neck cancer, particularly oral cancer. In recent years a growing number of studies indicate that oral microbiota could be involved in the development of primary tumours outside of head and neck region. The aim of this article is to review the recent studies based on high-throughput technology to present evidences of a relationship between oral microbiota and “non-head and neck tumours.” Oral dysbiosis seem to be more pronounced in patients with tumours of gastrointestinal tract, in particular oesophageal, gastric, pancreatic, and colorectal cancers, paving the way for developing specific oral microbiota test to allow early cancer detection. Regarding other tumour types, the results are promising but highly preliminary and still debated. Currently, there are several factors that limit the generalization of the results, such as the small sample size, the lack of adequate clinical information about patients, the different sequencing techniques used, and biological sample heterogeneity. Although only at the beginning, the analysis of oral microbiota could be the next step in the evolution of cancer therapy and will help clinicians to develop individualised approaches to cancer prevention and treatment.